2021
DOI: 10.1088/1361-648x/abe6e1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties across different coarse-grained models for ionic liquids

Abstract: Room-temperature ionic liquids (RTILs) stand out among molecular liquids for their rich physicochemical characteristics, including structural and dynamic heterogeneity. The significance of electrostatic interactions in RTILs results in long characteristic length-and timescales, and has motivated the development of a number of coarse-grained (CG) simulation models. In this study, we aim to better understand the connection between certain CG parameterization strategies and the dynamical properties and transferab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 112 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…As already discussed in the previous section, one key to reducing the dynamic consistency problem is accurate structural coarse-graining, as it helps to recover consistent dynamics even in standard MD simulations, i.e., consistent barrier crossing dynamics and consistent relative speedup. , In fact, using kinetic information as additional input for the parametrization of coarse-grained force fields may improve their quality, , because it gives more weight to transitional conformations, which are typically not well sampled in standard coarse-graining approaches. For instance, Xia, Keten and co-workers have recently proposed an “energy renormalization” method for adjusting the activation barriers in CG models of polymer glasses, which allows to recover the dynamical and rheological properties obtained from all-atom reference simulations over a wide temperature range. …”
Section: Scale-bridging Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As already discussed in the previous section, one key to reducing the dynamic consistency problem is accurate structural coarse-graining, as it helps to recover consistent dynamics even in standard MD simulations, i.e., consistent barrier crossing dynamics and consistent relative speedup. , In fact, using kinetic information as additional input for the parametrization of coarse-grained force fields may improve their quality, , because it gives more weight to transitional conformations, which are typically not well sampled in standard coarse-graining approaches. For instance, Xia, Keten and co-workers have recently proposed an “energy renormalization” method for adjusting the activation barriers in CG models of polymer glasses, which allows to recover the dynamical and rheological properties obtained from all-atom reference simulations over a wide temperature range. …”
Section: Scale-bridging Strategiesmentioning
confidence: 99%
“…Since forces drive the dynamics, it becomes more difficult to restore the correct dynamical properties without further adjustments. Indeed, recent studies on ionic liquids 374 have suggested that structure-based CG models tend to have a more consistent dynamical behavior than thermodynamically CG models, e.g., regarding the relative mobility of anions and cations. We will specifically discuss issues of dynamic coarsegraining in the next section.…”
Section: IIImentioning
confidence: 99%
“…Previous work has suggested that the inclusion of the bond interactions, even after subtracting their contribution to the mean force, can provide numerical stability for determining optimal nonbonded parameters. [65][66][67] All pairwise interactions were represented with radially-isotropic fourth-order basis splines with control points spaced every 0.01 nm ranging from 0.0 to 1.4 nm. In this fashion, a set of CG pairwise potentials was generated for each mapping at each state point.…”
Section: G Applying the Multi-scale Coarse-graining Techniquementioning
confidence: 99%
“…31 ILs exist as viscous liquids below 100 °C and are composed of bulky, asymmetric cations and anions. [32][33][34] Coordinating interactions between the cation and anion direct the biophysical and physicochemical properties within the ILs and the resulting interactions with the external microenvironment. Thus, structural alterations to the cation or anion, (e.g., alkyl chain length, functionalization with chemical moieties, branching, or steric organization) [35][36][37][38][39][40][41][42] can cause radical changes in bulk properties of ILs and their interplay with other biomolecules.…”
Section: Introductionmentioning
confidence: 99%